Comparison of Sensory and Motor Innervation Between the Acupoints LR3 and LR8 in the Rat With Regional Anatomy and Neural Tract Tracing - Xu, Dongsheng; Zou, Ling; Zhang, Wenjie; Liao, Jieying; Wang, Jia; Cui, Jingjing; Su, Yuxin; Wang, Yuqing; Guo, Yating; Shen, Yi; Bai, Wanzhu (Frontiers in Integrative Neuroscience, 2021)
Objective This study aimed to investigate the sensory and motor innervation of “Taichong” (LR3) and “Ququan” (LR8) in the rat and provide an insight into the neural relationship between the different acupoints in the same meridian. Methods The LR3 and LR8 were selected as the representative acupoints from the Liver Meridian and examined by using the techniques of regional anatomy and neural tract tracing in this study. For both acupoints, their local nerves were observed with regional anatomy, and their sensory and motor pathways were traced using neural tract tracing with single cholera toxin subunit B (CTB) and dual Alexa Fluor 594/488 conjugates with CTB (AF594/488-CTB). Results Using the regional anatomy, the branches of the deep peroneal nerve and saphenous nerve were separately found under the LR3 and LR8. Using single CTB, the sensory neurons, transganglionic axon terminals, and motor neurons associated with both LR3 and LR8 were demonstrated on the dorsal root ganglia (DRG), spinal dorsal horn, Clarke’s nucleus, gracile nucleus, and spinal ventral horn corresponding to their own spinal segments and target regions, respectively. Using dual AF594/488-CTB tracing, it was shown that the sensory and motor neurons associated with LR3 were separated from that of LR8. Conclusion This study demonstrates that LR3 and LR8 are innervated by different peripheral nerves, which originated from or terminated in their corresponding spinal segments and target regions independently through the sensory and motor pathways. These results provide an example for understanding the differential innervation between the different acupoints in the same meridian.